The Role of Teachers in Improving the Discipline Character of Students - Subiarto, Subiarto; Wakhudin, Wakhudin (Universitas Muhammadiyah Purwokerto, 2021)
This study aimed to examine and describe the role of the teacher in improving the character of discipline for students. This research is a descriptive qualitative research. The research subjects were the principal, teachers, and students. The data collection techniques used were interviews, observation, and documentation. Data analysis was performed using qualitative descriptive analysis techniques. The results of this study indicated that the role of teachers in the character building of student discipline at SD Negeri 1 Kendaga is a teacher as an educator, a teacher as ainstructor, a teacher as a guide, a teacher as a trainer, and a teacher as an evaluator. The teacher's efforts in shaping student character are by using the method of habituation, exemplary, lectures and simulations.This research is useful for teachers, to be able to act as good role models, to provide guidance and supervision to improve students discipline.